GAS CONTENT OF THE ARTEMIVSK AREA TIGHT ROCKS IN THE SOUTHEASTERN DNIEPER-DONETSK DEPRESSION - Dudnikov, M.; Mykhailov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the article is to consider the geological structure and oil and gas content of the Artemivsk area. Previous geological exploration revealed traces of oil and gas in the Middle Carbonic Moscovian sediments. A complex analysis of field geophysical survey data allowed the authors to identify numerous gas saturated tight reservoirs in the Artemivsk area. The technique included a complex interpretation of well-logging and mud-logging data, results of core analysis and a description of thin rock sections. The obtained results suggest that there is a strong likelihood of discovering new unconventional gas fields in the Artemivsk area. There has been confirmed the presence of oil and gas in the tight Middle Carbonic rocks of the southeastern Dnieper-Donetsk Depression. These sediments were earlier considered as lacking prospects of having hydrocarbon deposits, hence the scientific novelty of the research. Further inquiry concerning the adjacent subsurface sites can be expected to produce new interesting findings. The presence of oil and gas in the Artemivsk area, which has been identified, expands the hydrocarbon resource base of the southeastern Dnieper-Donetsk Depression. A practical application of the authors’ recommendations combined with modern hydrocarbon exploration and production technologies will facilitate detecting new gas fields and increase its production.